2023
DOI: 10.1371/journal.pone.0276822
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of functional outcome in patients with major depression and bipolar disorder: A dynamic network approach to identify distinct patterns of interacting symptoms

Abstract: The purpose of this study is to use a dynamic network approach as an innovative way to identify distinct patterns of interacting symptoms in patients with Major Depressive Disorder (MDD) and patients with Bipolar Type I Disorder (BD). More precisely, the hypothesis will be testing that the phenotype of patients is driven by disease specific connectivity and interdependencies among various domains of functioning even in the presence of underlying common mechanisms. In a prospective observational cohort study, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The network analysis conducted on the whole sample (Figure 1, left side) showed that in patients with MDD, there is a separation between the neurocognitive and psychosocial domains (Platania et al, 2023). The latter also includes the two nodes assessing depression: HDRS (Node 7) and BDI‐II (Node 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The network analysis conducted on the whole sample (Figure 1, left side) showed that in patients with MDD, there is a separation between the neurocognitive and psychosocial domains (Platania et al, 2023). The latter also includes the two nodes assessing depression: HDRS (Node 7) and BDI‐II (Node 8).…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on diagnostic protocols, it is interesting to note that HDRS seems to correlate better (Table 2) with the presence of ‘suicide attempts’ when compared to the BDI‐II. This finding can be explained in various ways: several studies demonstrate that HDRS seems to be a psychometric tool more sensitive for MDD, while BDI‐II is a more efficient assessment tool for bipolar depression (Carneiro et al, 2015; Guerrera et al, 2023; Hunt et al, 2003; Platania et al, 2023; Rush et al, 1986). This is due to both the different markers of the pathologies and the uneven subjective experience felt by patients, differently represented by the tests (Platania et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These data are in agreement with previous scientific evidence. In fact, with the pandemic’s progression, students and females showed greater levels of stress, depression, and anxiety that needed specific interventions for cognitive, affective, and psychosocial symptoms [ 46 , 47 , 48 ]. It should also be noted that our investigation highlighted a significant sex difference regarding stress levels, while in the validation study of the M.S.P.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the Montreal Cognitive Assessment (MoCA) [ 4 ] is a global measure of cognition that has shown high sensitivity and specificity in detecting Mild Cognitive Impairment (MCI), while other specific cognitive domains and neuropsychiatric symptoms should be considered to give clearer a picture into person’s intrinsic capacity [ 5 ], in particular executive functions [ 6 ] and affective symptoms such as depression [ 7 ].…”
Section: Introductionmentioning
confidence: 99%